دور نظم المعلومات الإدارية في تعزيز كفاءة أداء إدارة الموارد البشرية (Comprehensive Journal of Science, 2026)
Management Information Systems (MIS) are a critical factor in enhancing the efficiency of Human Resource Management (HRM) performance in modern organizations. These systems play a central role in improving planning, recruitment, training, performance evaluation, and motivation processes by providing accurate and reliable data in a timely manner, contributing to effective administrative decision-making. This study aims to analyze the role of MIS in supporting the efficiency of HRM performance, based on a descriptive analytical approach applied to a group of HRM staff members. The results showed that MIS contribute to improving operational processes and enhancing decision-making, which positively affects individual and collective performance within organizations. The study concluded that there is a need to develop the technological infrastructure of these systems and train employees to use them optimally.
Keywords: Management Information Systems, Human Resource Management, Performance Efficiency, Planning, Recruitment, Training, Performance Evaluation, Motivation, Decision Making